Practical and professional ethics : key concepts - Robison, Wade L. (London, England : Zed Books, 2021)
"Before we can resolve or avoid an ethical dilemma, we need to understand what makes something ethical. Practical and Professional Ethics : Key Concepts introduces us to a series of real cases where the stakes can be high, the situations complex, and the ethical issues often difficult to see. Drawing on examples from medicine, law and science, it offers a practical approach to thinking critically about the ethical problems that occur in our professions, teaching us how to: focus on the ethical aspects of any situation distinguish between different kinds of ethical problems tailor our response to the kind of problem we face construct arguments we can plausibly attribute to those involved identify the role of power, discretion and moral blindness By guiding us through the concepts, issues and skills at play when we face an ethical problem, we learn how to find a solution. Ideal for students or professionals, this book provides the grounding required to become a more complex moral thinker, a quality that can be applied in a number of fields and jobs"--
Introduction -- 1. Objects of Ethical Concern -- 2. Making Ethical Judgments -- 3. Professions -- 4. Norms and Professional Codes of Ethics -- 5. Virgin Eyes: Seeing from Other Points of View -- 6. Understanding Cases -- 7. Kinds of Ethical Problems -- 8. Internal and External Moral Problems -- 9. Fundamental Moral Relations 10.Discretion 11.Rules of Skill 12.Rules of Skill, Yet Again 13.Professional Character 14.Social Responsibilities 15.Concluding Remarks Bibliography Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Professional ethics; Ethics & moral philosophy; Electronic books